TRADISI MANCAK DALAM UPACARA PERNIKAHAN DI PULAU SEPANJANG KECAMATAN SAPEKEN: KAJIAN NILAI PENDIDIKAN BUDAYA DAN PELESTARIANNYA DI KALANGAN GENERASI MUDA - Lukman Hidayat; Moh. Fauzi; Ahmad Yasid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the existence of the mancak tradition in wedding ceremonies on Sepanjang Island, Sapeken District. Mancak , a traditional martial art, holds a significant place in local customs and is considered essential during wedding rituals. It is believed that performing mancak during a wedding brings blessings and good fortune to the newlyweds. The purpose of this research is to explore the cultural values embedded in the mancak tradition, its role in education and cultural identity, and the factors contributing to its preservation among the younger generation. Using a descriptive and ethnographic approach, data were collected through direct interviews and field observations. The findings reveal that despite modern influences, the mancak tradition continues to thrive due to the strong belief system of the community and its transmission through generations. The tradition serves not only as a form of entertainment but also as a medium for instilling cultural pride and historical awareness. Local communities actively preserve mancak by integrating it into wedding ceremonies and encouraging youth participation through informal education and community-based cultural programs.